Hired guns views about armed contractors in Operation Iraqi Freedom - Cotton, Sarah K.; ebrary, Inc. (Santa Monica, CA : RAND, 2010)
The use of armed private security contractors (PSCs) in the Iraq war has been unprecedented. Not only government agencies but also journalists, reconstruction contractors, and nongovernmental organizations frequently view them as a logical choice to fill their security needs, yet there have been a number of reports of PSCs committing serious, and sometimes fatal, abuses of power in Iraq. This study uses a systematic, empirically based survey of opinions of U.S. military and State Department personnel on the ground in Iraq to shed light on the following questions: To what extent are armed PSCs perceived to be imposing costs on the U.S. military effort? If so, are those costs tempered by positive contributions? How has the use of PSCs affected U.S. military operations in Operation Iraqi Freedom? While the military personnel did report some incidents of unnecessarily threatening, arrogant, or belligerent contractor behavior, the survey results indicate that neither the U.S. military nor State Department personnel appear to perceive PSCs to be "running wild" in Iraq. Moreover, respondents tended to consider PSCs a force multiplier rather than an additional strain on military troops, but both military and State Department respondents held mixed views regarding the contribution of armed contractors to U.S. foreign policy objectives.
Introduction -- Private military and security contractors are not a new phenomenon : a brief history of military privatization -- Do private security contractors have a negative impact on military retention and morale? -- Have private security contractors had an adverse effect on local Iraqis' perceptions of the entire occupying force because of the legal impunity with which they operated in Iraq prior to 2009? -- Is there a relative lack of unit cohesion and systematic coordination between private security contractors and the military? -- Do private security contractors play a valuable supporting role to the U.S. military as a force multiplier? -- Do private security contractors provide skills and services that the Armed Forces lack? -- Do private security contractors provide vital surge capacity and critical security services? -- Summary of findings and policy recommendations.
Includes bibliographical references.
Electronic reproduction.
Keywords: Postwar reconstruction -- Iraq -- Evaluation; Private military companies -- Iraq -- Evaluation; Private security services -- Iraq -- Evaluation; Government contractors -- Iraq -- Evaluation; Contracting out -- Iraq -- Evaluation; Government contractors -- United States -- Evaluation; Contracting out -- United States -- Evaluation; Electronic books